New-Dialect Formation : the Inevitability of Colonial Englishes. - Tridgill, Peter (Edinburgh University Press, 2006)
This book presents a new and controversial theory about dialect contact and the formation of new colonial dialects. It examines the genesis of Latin American Spanish, Canadian French and North American English, but concentrates on Australian and South African English, with a particular emphasis on the development of the newest major variety of the language, New Zealand English. Peter Trudgill argues that the linguistic growth of these new varieties of English was essentially deterministic, in the sense that their phonologies are the predictable outcome of the mixture of dialects taken from the.